2014
DOI: 10.1177/0004563214521795
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase-associated lipocalin as a biomarker of acute kidney injury: a critical evaluation of current status

Abstract: Background The early prediction of acute kidney injury (AKI) by current clinical and laboratory methods remains inadequate. Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as a promising non-invasive biomarker of kidney injury. We systematically reviewed the utility of plasma and urine NGAL measurements for the prediction of AKI in humans. Methods We searched MEDLINE, PubMed and EMBASE for human biomarker studies that included NGAL (January 2005 to October 2013). Studies reporting on the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
173
4
20

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(203 citation statements)
references
References 102 publications
(145 reference statements)
6
173
4
20
Order By: Relevance
“…We found that urinary NGAL was significantly higher in infants who suffered impaired renal function than in healthy controls. 15 In adults, NGAL is a biomarker for acute renal injury 16 and it is useful to evaluate the risk of DGF after kidney transplantation. 9,10 NGAL increase occurs rapidly after acute injury, and is detectable within a few hours, characterizing NGAL as a troponin-like molecule for an early and sensitive reflection of kidney function, better than serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that urinary NGAL was significantly higher in infants who suffered impaired renal function than in healthy controls. 15 In adults, NGAL is a biomarker for acute renal injury 16 and it is useful to evaluate the risk of DGF after kidney transplantation. 9,10 NGAL increase occurs rapidly after acute injury, and is detectable within a few hours, characterizing NGAL as a troponin-like molecule for an early and sensitive reflection of kidney function, better than serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…12 Both urinary NGAL and plasma NGAL have been extensively investigated as reliable biomarkers in several clinical conditions, including cardiac surgery-related AKI, poor renal function in very low birth weight infants, critically ill patients, and DGF in kidney transplantation. [13][14][15][16] In addition, we have recently described the ability of NGAL to induce immune tolerance by upregulating human leukocyte antigen (HLA-G) expression and expansion of T-regulatory cells in healthy donors, providing the basis for further studies to evaluate its possible role in immunomodulation and tolerance induction in transplant recipients. 17 This mounting evidence led to evaluate the role of NGAL after kidney transplant.…”
mentioning
confidence: 99%
“…As first highlighted by Mishra et al, 25 a dramatic increase in both urine and plasma NGAL is detected within 2-6 hours of CPB in children destined for AKI, with a predictive area under the receiver operating characteristic curve (AUC) of >0.9. These findings have now been confirmed in >7500 patients, [26][27][28] with measurements obtained within 4-6 hours after initiation of CPB, yielding an overall predictive pooled AUC of 0.86. The predictive performance for CS-AKI was similar for both urine and plasma NGAL.…”
mentioning
confidence: 65%
“…The ability of NGAL to predict AKI in this heterogeneous population has been confirmed in >8500 critically ill patients, 27 with measurements obtained within 6 hours of clinical presentation yielding an overall predictive AUC of 0.8. 11 In a recent meta-analysis 28 specifically examining the value of NGAL for the prediction of AKI in patients with sepsis, the specificity of plasma NGAL for predicting AKI was inferior to that of urine NGAL in sepsis, although the sensitivities and pooled AUCs were similar and promisingly high (0.8-0.9).…”
mentioning
confidence: 89%
“…The NGAL fulfils many of the characteristics important for a useful AKI biomarker. NGAL represents a significant component in the pathophysiology of the disease [17,18]. Furthermore, NGAL incrementally adds value to the baseline clinical risk assessment, potentially enabling physicians to intervene early to limit the extent of renal injury [19].…”
Section: Introductionmentioning
confidence: 99%